Pelatihan Penyusunan Rancangan Penelitian Tindakan bagi Guru Bimbingan dan Konseling SMA di Kabupaten Tanggamus - Syarifuddin Dahlan; Ranni Rahmadiyanthi; Citra Abriani M.; Rahmat Hermawan (Jurusan Ilmu Pendidikan - Universitas Lampung, 2022)
Guidance and Counseling Teachers should be accustomed to conducting action research. In fact, BK teachers have not been able to design and carry out research in accordance with the rules and principles of an action research. This training aims to improve the ability of BK teachers to design action research in the field of guidance and counseling. The training was carried out in Tanggamus District using a work-assignment learning method in the form of a workshop and was attended by 40 high school guidance and counseling teachers. The activity begins with briefing and continues with the practice of preparing research proposals in a guided manner. Evaluation of the achievement of activities is carried out to check the level of teacher skills in preparing action research designs correctly using the Action Research Design Quality Assessment Form. The results of the activity showed that in general the skills of the participants had improved. They have been able to formulate the title, problem, objective, and research methodology correctly. Participants categorized as